The comparative effects of ventilation shutdown with heat (VSDH), relative humidity (VSDHRh), or CO2 (VSDCO2) on broiler electroencephalogram (EEG), blood chemistry and gene expression - Kari L. Harding; Emmillie Boot; Jackson O. Evans; Sanjay B. Shah; Ramon D. Malheiros; Kenneth E. Anderson (Journal of Applied Poultry Research)
Summary: Highly Pathogenic Avian Influenza (HPAI) outbreaks have highlighted major needs for multiple effective depopulation methods across all sectors and housing systems in the commercial poultry industry. Ventilation shutdown plus heat (VSDH), heat and relative humidity (VSDHRh), and carbon dioxide (VSDCO2) were analyzed to understand how these methods affect broiler stress parameters and behavior. Two phases were used with both phases being conducted in sealable Plexiglass® chambers. Phase 1 (P1) analyzed electroencephalogram (EEG) of each broiler in each treatment along with blood chemistry, corticosterone, and heat shock protein 70 (HSP70) at time of death (TOD). Phase 2 (P2) looked at the progression of the stress parameters over time with specific physiological points when birds were removed from their respective chamber. There was a significant difference (P<0.0001) between time of death (TOD) with VSDCO2 being significantly faster at 21.25 minutes compared to VSDH and VSDHRh at 63.75 and 58.25, respectively, in P1. However, there were no significant differences in the TOD between VSDH or VSDHRh. There was also a significant increase in chamber ending CO2, for VSDCO2 compared to VSDH and VSDHRh. However, both VSDH and VSDHRh broilers had significantly greater (P<0.0001) post core body temperatures indicating hyperthermia being the mode of action rather than hypoxia which is the mode of action in VSDCO2. The HSP70 levels were significantly greater in VSDH at 1.23 CT-1 compared to both VSDHRh at 0.98 CT-1 and VSDCO2 at 0.90 CT-1, which were not significantly different from each other. Blood chemistry parameters that were significantly higher in VSDCO2 treatment broilers when compared to VSDHRh were total CO2 (TCO2), partial pressure of CO2 (pCO2), partial pressure of oxygen (pO2), Bicarbonate (HCO3), and blood oxygen saturation (sO2). When compared to VSDH, TCO2, pCO2, and sO2 levels were significantly greater in broilers undergoing the VSDCO2 treatment. There were also no significant differences in corticosterone between treatments in P1 with corticosterone levels for VSDH being 0.11 ng/mL, 0.10 ng/mL for VSDHRh, and 0.12 ng/mL for VSDCO2. When analyzing the effects of these treatments on broilers over time in P2, there were no significant differences in corticosterone, blood chemistry, or HSP70 when compared within their respective treatments. Based on this research, VSDHRh may be an effective and useful depopulation method that may be used in the event of an outbreak. This is due to the equivalency of TOD in comparison to VSDH, with potential reduction in HSP70 levels. More research should be conducted on the effects of VSDHRh, especially in a non-environmentally controlled setting.